2016
DOI: 10.1111/1440-1681.12511
|View full text |Cite
|
Sign up to set email alerts
|

Effects of captopril, telmisartan and bardoxolone methyl (CDDO‐Me) in ischemia‐reperfusion‐induced acute kidney injury in rats: an experimental comparative study

Abstract: Renal ischemia-reperfusion (IR) injury is one of the most common causes of acute kidney injury. This study investigated the effects of captopril (CAP), telmisartan (TEL) and bardoxolone methyl (BM) in animals with renal IR injury. Adult male Wistar-Albino rats were divided into six groups: control, vehicle, IR, IR with CAP, IR with TEL and IR with BM. Before IR was induced, drugs were administered by oral gavage. After a 60-min ischemia and a 120-min reperfusion period, bilateral nephrectomies were performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 55 publications
1
18
0
1
Order By: Relevance
“…These results are confirmed in a rat model of I/R where pre-treatment few hours before injury with CDDO-methyl ester reduces early renal damage by reducing oxidative stress and increasing antioxidant defence (151). These studies demonstrate that CDDO derivatives have the potential to be used in clinic to reduce renal IR injury through antioxidant effects.…”
Section: B) Activators Of Nrf2 Pathwaysupporting
confidence: 55%
“…These results are confirmed in a rat model of I/R where pre-treatment few hours before injury with CDDO-methyl ester reduces early renal damage by reducing oxidative stress and increasing antioxidant defence (151). These studies demonstrate that CDDO derivatives have the potential to be used in clinic to reduce renal IR injury through antioxidant effects.…”
Section: B) Activators Of Nrf2 Pathwaysupporting
confidence: 55%
“…Alterations in the RAS have been shown to contribute to the development of AKI and are associated with adverse outcomes both in experimental and clinical studies [45][46][47][48][49][50]. Several components of the kidney RAS, such as urine Angiotensinogen and Ang II, the main active peptide, are increased in experimental AKI caused by ischemia-reperfusion AKI [45][46][47][51][52][53][54][55][56] ACE inhibitors (ACEi) and angiotensin receptor antagonists (ARBs) may attenuate renal inflammation, injury and improve renal function in the ischemia-reperfusion model of AKI [57][58][59][60]. Intrarenal Ang II is reportedly elevated in AKI, which may worsen kidney tissue injury independently of its hemodynamic effect that helps maintain renal circulation [61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2, a cap'n'collar (CNC) basic-region leucine zipper (bZIP) transcription factor, influences intrinsic resistance to oxidative stress by inducing a battery of ROS-detoxifying enzymes and stimulates the production of antioxidants, including the tripeptide glutathione (GSH), thioredoxin (TXN), and sulfiredoxin (SRXN), all of which can reduce oxidized protein thiols [ 28 30 ]. A previous study demonstrated that the unbalanced redox state after IRI can be restored by the Nrf2 inducer and kidney injury can be alleviated by enhancing ROS detoxification [ 31 34 ]. These data suggest that the Nrf2 pathway is essential in protecting kidney against IRI.…”
Section: Discussionmentioning
confidence: 99%